2022
DOI: 10.3390/metabo12111151
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Series Metabolomic Analysis of SARS-CoV-2 Infection in a Ferret Model

Abstract: The global threat of COVID-19 has led to an increased use of metabolomics to study SARS-CoV-2 infections in animals and humans. In spite of these efforts, however, understanding the metabolome of SARS-CoV-2 during an infection remains difficult and incomplete. In this study, metabolic responses to a SAS-CoV-2 challenge experiment were studied in nasal washes collected from an asymptomatic ferret model (n = 20) at different time points before and after infection using an LC-MS-based metabolomics approach. A mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The integration not only indicated the key microbiome species impacted, but it also helped to filter the most significant redox pathways impacting the gut–liver axis. Similar strategies have been further employed to understand the extra-gut mechanism of FGIDs, such as IBS, functional dyspepsia [ 124 ], and infections such as SARS-CoV2 [ 125 , 126 ]. In the area of the nutritional impacts of prebiotics and probiotics, the study reported by Shinde, et al [ 64 ] included the combined approach of immunohistochemistry, enzyme kinetics, and metabolomics, including SCFA analytics.…”
Section: Application Of Multiomics In High-throughput Analysis Of Gut...mentioning
confidence: 99%
“…The integration not only indicated the key microbiome species impacted, but it also helped to filter the most significant redox pathways impacting the gut–liver axis. Similar strategies have been further employed to understand the extra-gut mechanism of FGIDs, such as IBS, functional dyspepsia [ 124 ], and infections such as SARS-CoV2 [ 125 , 126 ]. In the area of the nutritional impacts of prebiotics and probiotics, the study reported by Shinde, et al [ 64 ] included the combined approach of immunohistochemistry, enzyme kinetics, and metabolomics, including SCFA analytics.…”
Section: Application Of Multiomics In High-throughput Analysis Of Gut...mentioning
confidence: 99%